One Patient Is Not One Condition: Delivering Patient-Centered Care to Those With Multiple Chronic Conditions. (July 2017) - Liska, Jan; Beal, Anne
While patients with multiple chronic conditions account for the bulk of health care spending in many countries—71 cents of every dollar spent on US Medicare beneficiaries—medical research and care remain organized around singular diseases and specialties. This siloed approach places the burden of managing multiple conditions on patients, who often have difficulty navigating the health care system and following treatment recommendations. This helps explain why patients with multiple chronic conditions have more unplanned admissions to the hospital, worse health outcomes, and poorer quality of life. Longer life expectancies, aging populations, and the increasing incidence of chronic conditions will vastly increase the number of patients living with multiple conditions, placing strains not only on patients but on governments and businesses paying for their care. In Japan, for example, the elderly will make up more than a quarter of the population by 2018, putting tremendous pressure on the country's health system as chronic diseases become more prevalent with age.  Pharmaceutical companies can play a pivotal role in addressing these issues by developing products, programs, and services geared to the unique physical, social, and emotional challenges patients with multiple chronic conditions face. Companies also can have a significant impact by promoting collaboration and communication among health system stakeholders, expanding the knowledge base about patients' experiences with multiple chronic conditions, and developing therapies and tools to help patients adhere to treatments and improve their quality of life.